Temporary Shelter Applications After the February 6, 2023, Earthquake: Gaziantep Nurdağı Example - Cafer Giyik (Doğal Afetler ve Çevre Dergisi)
Disasters are the consequences of natural, technological, or anthropogenic events that directly or indirectly cause physical, economic, social, and environmental losses on people and human settlements, and affect communities by stopping or interrupting normal life and human activities. Though there are several natural disasters, earthquakes cause the most damage in Turkey in terms of damage rate and number of people affected. On the other hand, landslides, floods, rockfalls, avalanches and forest fires also cause considerable damage and economic losses. In Turkey, which is an earthquake-prone country, two devastating earthquakes with a magnitude of 7 Mw in Kahramanmaraş and 7.6 Mw in Hatay Kırıkhan occurred on 6 February 2023. While these earthquakes were effective in Malatya, Kahramanmaraş, Adıyaman, Gaziantep, Şanlıurfa, Diyarbakır, Hatay, Adana, Osmaniye, Kilis and surrounding counties, 50,399 people lost their lives and 1,279,727 structures (independent units) were damaged. The aim of this study is to determine what has been done within the scope of post-disaster temporary shelter applications in disaster areas and which methods were used to create these areas. In the study, temporary sheltering practices in Nurdağı District of Gaziantep province, one of the settlements most affected by the earthquake, were examined. In this context, evaluations were made regarding the qualifications, adequacy level and functions of prefabricated and temporary shelter areas such as tents, containers and masonry structures created in the district.